Mechanization of Sugarcane Planting - Singh, A K; Singh, Sukhbir (Indian Farming, 2017)
Mechanization of sugarcane planting facilitates timely completionof different operations with reduced labour, human drudgery and cost of operation. Furrow method of planting in deep furrows has beenfound superior in comparison to flat method of planting in terms ofincreased yield, reduced lodging and better ratooning due to deep rooting of crop. This method also facilitates furrow irrigation which increases irrigation water use efficiency (IWUE) and saves irrigation water.